2023
DOI: 10.1029/2022jg007032
|View full text |Cite
|
Sign up to set email alerts
|

A Spatially Integrated Dissolved Inorganic Carbon (SiDIC) Model for Aquatic Ecosystems Considering Submerged Vegetation

Abstract: Extreme weather events and natural disasters have occurred worldwide due to global warming, underscoring the urgent necessity of climate change mitigation (IPCC, 2014, 2018, 2021). Nellemann et al. (2009 have shown that much of the Earth's carbon is captured and stored naturally as "blue carbon" in oceanic and coastal ecosystems, with vegetated habitats, such as mangroves and submerged aquatic vegetation (SAV), accounting for more than 50% of all carbon storage in ocean sediment. Previous studies have shown th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…Regarding the DIC uptake by SAVs, a DIC equation was proposed by Nakayama et al (2020a) [ 6 ]; to understand the effect of Zostera Marina on DIC sequestration in Komuke Lagoon [ [39] , [40] , [41] , [42] ]. In contrast, Nagatomo et al (2023) [ 43 ]; proposed a DIC equation for Potamogeton crispus in Australia's freshwater lake, Lake Monger. They found that P. crispus has a higher potential to capture DIC than Z. marina .…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the DIC uptake by SAVs, a DIC equation was proposed by Nakayama et al (2020a) [ 6 ]; to understand the effect of Zostera Marina on DIC sequestration in Komuke Lagoon [ [39] , [40] , [41] , [42] ]. In contrast, Nagatomo et al (2023) [ 43 ]; proposed a DIC equation for Potamogeton crispus in Australia's freshwater lake, Lake Monger. They found that P. crispus has a higher potential to capture DIC than Z. marina .…”
Section: Discussionmentioning
confidence: 99%